Pengaruh Badan Usaha Milik Desa Terhadap Kesejahteraan Masyarakat (Studi Kasus: Desa Sambirejo) - Dwisi, Septian; Astuti, Ismadiyanti Purwaning (EKOBIMA, 2024)
Sambirejo Village is a village located in Prambanan District, Sleman Regency, Special Region of Yogyakarta and is separated directly from Klaten Regency. Sambimulyo Village has a BUMDes. BUMDes is a business entity managed by the village. Sambimulyo BUMDes has an important role in community welfare. This study aims to determine the effect of community income, the inhibiting factors of sambimulyo BUMDes, and the supporting factors of sambimulyo BUMDes on community welfare in Sambirejo Village. This research uses quantitative methods. With primary data obtained directly in the Sambirejo Village from the results of a questionnaire of 100 samples and observations. Data analysis was carried out using multiple regression analysis with IBM SPSS version 26 software. The results showed that before and community income had a positive and significant effect on community welfare, while the inhibiting factors for BUMDes sambimulyo were negative and significant for community welfare, supporting factors for BUMDes sambimulyo were positive and significant for welfare community, and there are differences before and after the Sambimulyo BUMDes through a different test which produces significant values.